Penguatan Literasi Digital pada Remaja (Cegah Cyberbullying dan KGBO) di Kota Banjarmasin: Strengthening Digital Literacy in Adolescents (Preventing Cyberbullying and KGBO) in Banjarmasin City - Akhmad, Bachruddin Ali; Astuty, Sri; Siswanto, Siswanto; Sarwani, Sarwani; Ainani, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to enhance digital literacy among the youth of Hasanuddin Madjedi Mosque in Banjarmasin, focusing on preventing cyberbullying and Online Gender-Based Violence (OGBV). Initial observations revealed that 95% of the mosque's youth use digital media but lack a comprehensive understanding of the negative impacts of harmful content, particularly related to cyberbullying and OGBV. The activity was conducted through a series of socialization and training sessions involving 40 youth participants. The methods included education, training on creating positive content, the application of technology utilizing digital platforms such as Instagram and TikTok, as well as post-activity mentoring and evaluation. The results demonstrated a significant improvement in participants' understanding of the dangers of cyberbullying and OGBV, along with their skills in producing positive digital content. This program is expected to serve as a model for digital literacy programs for other community groups, involving local communities and educational institutions.